Struktur Histopatologi Ginjal dan Hati Kambing Penderita Tripanosomiasis Pasca Pengobatan Berenil - M Lazuardi (Faculty of Animal Science, Bogor Agricultural University, 2008)
BerenilR (diminazene aceturate) is a chemotrypanocide and commonly used for treatment of protozoa infections as Babesiosis, Leishmaniasis and Trypanosomiasis in large animals. Indonesian government explained that the drug was never used before. Since 1999, Directorate of Livestock Services, Department of Agriculture, Republic of Indonesia recommended that the drug could be used for treatment of Trypanosomes cases. In contrast, the dosage level for the treatment of Trypanosomes was never determined before. In the late 2005, Indonesian researchers have investigated the new dosage of BerenilR for trypanosomes treatment. Base on the problem described above, the study was carried out to evaluate toxic effect of BerenilR to kidneys and livers. The objective of this study was to obtain the new data of toxic effect at multiple dosages. Ten Etawa breed goats were infected by Trypanosoma evansi Bangkalan isolate at more than 3.108 Trypanosoma/ml during the week. Five of ten subjects were treated by intramuscularly of BerenilR at multiple doses or superimpose dose (initial dosage 10.44 mg/kg body weight and four times of 7 mg/kg body weight every 31 minutes). Forty five days post treatment; the subjects were killed and the kidneys and livers were removed and preserved in 20% formalin. The histological specimens of their organs stained by haematoxylline eosin (HE) were examined by light microscope. There were no breakage on the histology structure of the Etawa breed goat kidneys and livers after treatment. It could be concluded that the BerenilR at multiple dosages was effective dose for treatment (P < 0.05) of Trypanosomes. Key words: diminazene aceturate, superimpose, goats, toxic effect, kidney, liver